Femoral fracture repair by demineralized bone matrix combinations in canines - SURESH KUMAR, R A; RAMAKRISHNA, O (The Indian Journal of Animal Sciences, 2014)
Autogenous cancellous bone and demineralized bone matrix combinations used in treatment of experimentally created femoral fractures with bone loss in 48 mongrel dogs of either sex divided equally into 4 groups. Group 1 was kept as control without any graft or implant, while group 2,3,4 animals received autogenous cancellous bone graft, demineralized bone matrix with tricalcium phosphate and demineralized bone matrix with hydroxyapatite implants respectively. Intramedullary pinning was used in all the groups for immobilization of fractured segments. Early functional limb usage was noticed in demineralized bone matrix with tricalcium phosphate implanted group followed by demineralized bone matrix with hydroxyapatite and autogenous cancellous bone grafted groups. Radiologically the segmental defect was visible clearly even up to twelfth week in control animals. Bridging of the gap and union of graft to host bone was observed at ninth week in cancellous bone grafted animals. The union was visible at sixth week in demineralized bone matrix implanted groups. Periosteal reaction was prominent in control and cancellous bone grafted animals. The presenUnvestigation proved the efficacy of DBM + TCP; DBM + HA implants as good substitutes for autogenous cancellous bone grafts in treating fractures with bone loss in animals.